Alkoxy/halostyryl benzoic acids: Synthesis, crystal structure, and study of mesomorphic and photophysical properties. (13th June 2017) - Muhammad, Khushi; Rauf, M. Khawar; Tahir, M. Nawaz; Hameed, Shahid
ABSTRACT: Alkoxy/halostyrylbenzoic acids were synthesized and evaluated for their mesomorphic and photophysical properties. The trans geometry of the molecules was established by the presence of large coupling constants in 1 H-NMR spectra and confirmed further by X-ray diffraction (XRD) analysis of two of the compounds. The straight-chain acids were found fairly stable showing first sign of decomposition above 290°C. The enantiotropic mesophases could only be studied in acids with seven or more methylene groups in the alkoxy chain. Textures of nematic and smectic phases were exhibited by these acids under polarizing optical microscope. Photophysical behavior of the compounds in solution was also investigated.